Laboratory examination of greenhouse gaseous and microbial dynamics during thawing of frozen soil core collected from a black spruce forest in Interior Alaska. Issue 6 (2nd November 2018) - Nagano, Hirohiko; Kim, Yongwon; Lee, Bang-Yong; Shigeta, Haruka; Inubushi, Kazuyuki
ABSTRACT: In this study, we conducted an incubation experiment on a frozen soil core collected from a black spruce forest in Interior Alaska, in order to investigate potential changes in greenhouse gaseous (GHG) and microbial dynamics during thawing of frozen soil. The soil thawing is an important environmental process determining the annual GHG balance in the northern high-latitude ecosystem. A core spanning the ground surface to upper permafrost with a depth of 90 cm was vertically grouped into three layers (top, middle, and bottom layers). Then, 12 soil samples from 3 layers (i.e., 4 soil samples per layer) were incubated for 3 weeks, and net carbon dioxide (CO2 ) and methane (CH4 ) release/uptake rates were estimated. During the incubation, temperature was changed weekly from 0 to 5, then 10°C. The net amounts of CO2 released by six of the eight soil samples from the top and middle layers were 1.5–19.2-fold greater at 5°C than at 0°C, while the release at 10°C was reduced in the cases of three of these six soil samples. Net CH4 release was the greatest in bottom-layer soil samples incubated at 0°C. Then, low but apparent CH4 release was observed in top and middle-layer soil samples incubated at 0°C. At 5 and 10°C, net CH4 release from bottom-layer soil samples was decreased. Then, net CH4 uptake was observed in the top and the middle-layer soil samples. Both net uptake and release of CH4 were reduced upon the addition of a chemical inhibitor (i.e., 2-bromoethane sulfonate) of anaerobic methanotrophic and methanogenic activity. The bacterial and archaeal community structures based on 16S rRNA amplicon analysis were changed along the depth, while they were less changed during thawing. Thus, it was found that soil GHG dynamics responded sensitively and variously to thawing, while there was less change in 16S rRNA-based microbial community structures during the thawing progress.